Economics of Energy Management in a Commune - Chosen Aspects - Kozłowski, Waldemar (Olsztyn Economic Journal, 2012)
Conditions of energy sector development correlated with shrinking resources of the conventional energy sources, increased importance of environmental policy as well as continual price increases cause that the territorial governments should, within the scope of their competences and abilities, rationalise energy consumption and costs. This paper presents the tools for energy sector rationalisation in a commune with consideration of the opportunities for optimisation of energy consumption costs within municipal resources by applying the ESCO model. The paper also draws attention to the possibility of utilising the resources of renewable energy sources by communal governments based on the example of wind energy, of which Warmia and Mazury has some of the largest resources in Poland.